Stigmasterol root exudation arising from Pseudomonas inoculation of the duckweed rhizosphere enhances nitrogen removal from polluted waters. (15th October 2021) - Lu, Yufang; Kronzucker, Herbert J.; Shi, Weiming
Abstract: Rhizospheric microorganisms such as denitrifying bacteria are able to affect 'rhizobioaugmention' in aquatic plants and can help boost wastewater purification by benefiting plant growth, but little is known about their effects on the production of plant root exudates, and how such exudates may affect microorganismal nitrogen removal. Here, we assess the effects of the rhizospheric Pseudomonas inoculant strain RWX31 on the root exudate profile of the duckweed Spirodela polyrrhiza, using gas chromatography/mass spectrometry. Compared to untreated plants, inoculation with RWX31 specifically induced the exudation of two sterols, stigmasterol and β-sitosterol. An authentic standard assay revealed that stigmasterol significantly promoted nitrogen removal and biofilm formation by the denitrifying bacterial strain RWX31, whereas β-sitosterol had no effect. Assays for denitrifying enzyme activity were conducted to show that stigmasterol stimulated nitrogen removal by targeting nitrite reductase in bacteria. Enhanced N removal from water by stigmasterol, and a synergistic stimulatory effect with RWX31, was observed in open duckweed cultivation systems. We suggest that this is linked to a modulation of community composition of nirS- and nirK- type denitrifying bacteria in the rhizosphere, with a higher abundance of Bosea, Rhizobium, and Brucella, and a lower abundance of Rubrivivax . Our findings provide important new insights into the interaction of duckweed with the rhizospheric bacterial strain RWX31 and their involvement in the aquatic N cycle and offer a new path toward more effective bio-formulations for the purification of N-polluted waters. Graphical abstract: Image 1 Highlights: Rhizospheric Pseudomonas inoculant strain RWX31 inoculation induces stigmasterol exudation in duckweed. Stigmasterol at low dose can function as an N-removal stimulant for strain RWX31. Stigmasterol enhances bacterial biofilm formation and nitrite reductase. Stigmasterol alters the composition of the nitrite-reducing bacterial community responsible for N removal. The stigmasterol/RWX31 pair significantly improves the rate of N removal in duckweed systems.